The European Union's global role in a changing world: Challenges and opportunities for the new leadership - Christine Hackenesch; Niels Keijzer; Svea Koch (German Institute of Development and Sustainability (IDOS), 2024)
This collective IDOS Discussion Paper seeks to inform the incoming EU leadership and member state capitals about the EU's role in a changing world, main internal and external influences, as well as the prospects and expected challenges in the new legislative period. The primary focus of this publication is on key challenges for the new EU leadership in the field of development policy. In addition, it analyses the interrelations between development policy and other external and internal EU policies and their influences on global sustainable development. The publication consists of 17 sections, which in addition have been published as long-reads on the IDOS website. The views expressed in the sections of this paper are the authors'.
Keywords: 320; European Union; European development policy; European Parliament